AKIBAT HUKUM PENERBITAN BILYET GIRO KOSONG DALAM PERSPEKTIF PERATURAN PERUNDANG-UNDANGAN DI INDONESIA (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2022)
Time by time was passed, human life has progressed. The transaction in the old sistem using barter, and now has changed to using money. The example one the money for transactions is bilyet giro. Bilyet giro is one of the paper for asking to move the money from sender's bank account to the receiver's bank account. The using of bilyet giro stil have some problem. Blank bilyet giro give some uncomfortable for the people, so we need to give the trust again from the people. Bilyet giro has a law relations by the maker, the receiver, ant the bank that have their account. In the law relations, they have something to do with the rights and obligations. Because of the debtor give the blank bilyet giro, that make some law is working to prove the problem. The law effect from debtor is to make debtor pay the debt to the creditor so they can get what must they have from the transaction with debtor. Bilyet giro maker will get the administrative penalty by the rules Bank Indonesia law number 8/29/Pbi/2006 about the national blacklist of the blank bilyet giro debtor that is the identity of bilyet giro maker will add to the blacklist and can't to use the bilyet giro, so they must to pay the penalty and the compensation just like what in the rule of civil law.